Lobar Torsion after Video-Assisted Thoracoscopic Lobectomy: 2 Case Reports - Duan, L.; Chen, X.; Jiang, G. (The Thoracic and Cardiovascular Surgeon, 2012)
Lung torsion is a rare but potentially lethal complication after pulmonary resection. We report two cases of right middle lobar torsion after video-assisted thoracoscopic (VATS) right upper lobectomy in our unit. The two cases were diagnosed definitely 7 and 14 days after VATS surgery by computed tomography (CT) scan and bronchoscopy, respectively. Rethoracotomy and right middle lobectomy were performed in both patients. VATS lobectomy contributes to the development of lobar torsion so this complication should be considered. Carefully checking anatomical structures before thoracotomic closure and correctly suturing the middle lobe to the consecutive lobe are effective ways to prevent this complication.
Keywords: thoracoscopy/VATS; surgery; complications; lung; benign or congenital lesions